Analysis of Elementary School Student Attitudes to Mathematics, Accelerated Learning Cycle (ALC) and Mathematical Questions - Fendrik, Muhammad; Prihandoko, Yogi; Wijaya, Tommy Tanu; Ahmad, Nur Jahan (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2024)
Many factors cause mathematics problems in elementary school students. Starting from learning, learning approaches, to questions related to mathematics. This research aims to analyze and describe students' attitudes towards mathematics, accelerated learning cycles, and mathematics questions. This research was conducted on fifth grade at one of the state elementary schools in Pekanbaru City, Riau Province. Data collection in this study used a Likert scale model by analyzing student responses through questionnaires on subject scores and neutral scores on teacher and student activity observation sheet data. Based on the results of research conducted on students, it shows that elementary school students show a positive attitude towards mathematics, learning using the Accelerated Learning Cycle (ALC) approach and mathematics questions. As for the findings obtained from the field, researchers suggest that teachers can use the ALC approach in the mathematics learning process, and get used to giving mathematical problems related to everyday life which can improve students' thinking abilities. The implication of this research is that the habituation of students’ positive attitudes towards mathematics, the ALC approach and mathematics questions can improve students' learning achievement in mathematics at school.